Proper waqf management and waqf accounting report: A mean to solve economic problems in Indonesia - Shariff, Ros Aniza Mohd; Fadhila, Zsa Zsa Indah (International Journal of Emerging Trends in Social Sciences, 2023)
This study aims to propose that a proper waqf management and waqf accounting practices in Indonesian waqf institutions will be one of the solutions for the economic problems. Data were collected through secondary data such as books, journals, and articles related to the waqf accounting or management. A proper waqf management and waqf accounting report is a crucial tool for achieving socioeconomic development and, if properly applied, may significantly contribute to the reduction of unemployment and the eradication of poverty, ultimately aiding in the socioeconomic advancement of Muslim communities. This study only focuses on waqf in Indonesia. Thus, the results of waqf may not be generalizable to other waqf in other countries or to privately managed waqf institutions. This study is expected to contribute to the improvement of waqf administration. The paper suggests a proper waqf management and waqf accounting report as a solution to the economic problems such as poverty, hunger and unemployment.